Babylonia 689-627 B.C.: A Political History - Frame, Grant
A Dissertation submitted to the Faculty of the Division of the Humanities in Candidacy for the Degree of Doctor of Philosophy; Dissertation Committee: J. A. Brinkman, Chairman; E. Reiner; S. Parpola.